Ordinances, of the Town of Columbia, (S. C.) Passed Since the Incorporation of Said Town: To Which are Prefixed, the Acts of the General Assembly, for Incorporating the Said Town, and Others in Relation Thereto, at 61-62, no. 41 (1823) - (:unkn) unknown (General Publisher, 1823)
That hereafter it shall not be lawful for any person to fire or discharge any gun, pistol or other small arms within the limits bounded by Henderson, Blossom, Lincoln and Upper streets
--
Keywords: DISCHARGE